Application of diversified health education in patients with brain tumor-related epilepsy and their family members (多元化健康教育在脑肿瘤相关性癫痫患者及其家属中的应用研究) - LIU Qiaojun (刘巧俊); YANG Fan (杨帆) (中西医结合护理)
Objective To explore the application effect of diversified health education inpatients with brain tumor-related epilepsy and their family members . Methods A total of 84 patients with brain tumor-related epilepsy and their family members admitted to hospital from January 2019 to December 2021 were selected as the research objects. According to the order of admission, patients were divided into control group and experimental group, with 42 cases in each group. The control group received routine health education, and the experimental group received diversified health education. The knowledge of epilepsy disease, medication compliance and family caregivers’ first aid skills of the two groups were compared. Results After intervention, the scores of disease cognition assessment and rate of medication compliance in the experimental group were higher than those in the control group ( P＜0. 05 ). The score of first aid skills assessment in the experimental group was higher than that in the control group, with a significant difference(P＜0. 01). Conclusion Diversified health education is conducive to improving the cognitive level of epilepsy knowledge and medication compliance of patients, and improving the epilepsy-related first aid skills of family caregivers. (目的 探讨多元化健康教育在脑肿瘤相关性癫痫患者及其家属中的应用效果。方法 选取科室2019年1月—2021年12月收治的84例脑肿瘤相关性癫痫患者及其家属作为研究对象, 按入院顺序将患者分为对照组及研究组, 各42例。对照组采取常规健康教育, 研究组采取多元化健康教育。比较两组患者癫痫疾病知识掌握情况、患者服药依从性及家属急救技能掌握情况。结果 干预后, 研究组患者疾病认知得分、患者服药依从性均高于对照组, 差异有统计学意义(P<0. 05); 研究组家属急救技能得分高于对照组, 差异有统计学意义(P<0. 01)。结论 多元化健康教育有利于提高患者癫痫疾病知识认知水平及服药依从性, 提升患者家属癫痫相关急救技能。)